Pelatihan digital entrepreneurship untuk memasuki pasar virtual: UMKM handycraft Desa Cileng, Kecamatan Poncol, Kabupaten Magetan - Widiasmara, Anny; Devi, Heidy Paramitha; Nurhayati, Puji; Aviyanti, Richo Diayan; Taufiq, Abd Rohman; Chairunnisa, Diaz Martha (Nur Science Institute, 2022)
The increase in the number of MSMEs will not contribute and sustain if MSMEs are not able to compete with the changing times. Internet of Things (IoT) is one form of changing times that has an impact on all aspects, including business. The impact of IoT on business is the shift of business from conventional business to digital business. MSMEs must respond to these business changes, one of which is by changing conventional marketing to digital marketing. The target of this PKM program is a group of MSMEs producing handicrafts in Cileng Village, Magetan which still lacks literacy about marketing and information technology. The purpose of this activity is to increase literacy on marketing strategies and information technology, develop marketing reach, and increase turnover. The method of service is mentoring and training. Mentoring and training related to product photos, making product descriptions using copywriting techniques, and opening an online store. The training program is expected to increase literacy knowledge about digital marketing, expand market reach, and fulfill the desired turnover target.